Analisa Dalil ‘Urf terhadap Ritual Panggih Manten dalam Tradisi Pernikahan Masyarakat Dusun Pengkol Kecamatan Mantingan - Teguh Eka Prasetya; Zahra Shoibatun; Iman Nur Hidayat; Rashda Diana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Indonesia is a country rich in cultural diversity, one of which is Javanese culture which is full of philosophical values ​​and symbolic meanings in every practice, including in the traditional wedding procession. One of the important rituals in Javanese traditional weddings is the Panggih Manten ritual, which represents the meeting between the bride and groom with various symbols of life, hope and blessings. Along with the development of the times and the flow of modernization, people's understanding of the philosophical meaning of the ritual has shifted. Some people still carry out this tradition as a hereditary custom without understanding the values ​​contained in it, even giving rise to debates regarding its suitability with Islamic teachings. This study aims to analyze the practice of the Panggih Manten ritual in Javanese traditional wedding traditions and review its suitability with the 'Urf argument in Islamic law. The research method used is qualitative with a juridical-normative approach, while the research location was carried out in Pengkol village, Mantingan District. The results of the study show that the Panggih Manten ritual is basically acceptable in Islamic law as long as it does not conflict with the principles of sharia. Based on analysis from the perspective of al-'urf, several aspects of the Panggih Manten ritual, such as muter asem (the act of making offerings), and the belief in disasters, contain elements that are inconsistent with Islamic law and could potentially lead to idolatry, thus being categorized as al-'urf al-fāsid. Therefore, the Panggih Manten tradition can be preserved through reinterpretation of its meaning and the elimination of elements that contradict Islamic teachings, thus aligning it with Islamic principles.